Sustainable development, energy dependence and the new profile electrical engineer (Publicaciones en Ciencias y Tecnología, 2011)
The engineering is considered as art, technology or the profession that seeks the transformation of natural resources for the benefit of society, hence the performance of the engineer must include skill, abilities and habits that enable them to go with technological advancement. However we notice that the measure displayed the scientific and technological advances have created problems for the environment and social welfare in general. The changing pace of the modern society and its environment, demands that university, in the case engineering, to adapt quickly to the needs of the society, all framed in sustainability. The electrical engineering in particularly, as professional responsible for responding generally to electrical systems, the framework of sustainable development and energy depended, develop skills with high social and environment sensitivity and efficiency criteria and ensure the welfare of future generation. In this sense, this research aims to highlight the importance in this profession and its relationship with the desirable future, including a lecture on sustainable development and social well is a stake and the new skills of these professionals.
Keywords: Energy dependece; sustainable development; electrical engineer; competences